2019
DOI: 10.3332/ecancer.2019.968
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colectomies associated with decreased retrieval of 12 or more lymph nodes compared to open in elective colon cancer surgery

Abstract: Background: Colorectal cancer is the third most commonly diagnosed cancer worldwide. Lymph node (LN) retrieval is a key factor for pathologic staging and prognosis of colorectal cancer. Increase in number of LNs removal suggests improvement in tumour clearance and decrease in metastatic spread. Studies have suggested that excising 12 or more LNs during colectomy in patients with colon cancer is associated with improved survival. To date, there have been no studies to determine whether minimally invasive surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In the meta-analysis, seven studies containing 23 297 patients with colorectal cancer revealed higher LN yield in the T3+T4 group than the T1+T2 group (OR=1.57, 95% CI (1.25 to 1.97), p<0.001, I 2 =70.46%) (figure 2 and online supplemental figure 11). 13 56–59 66 67 Likewise, four studies with 21 293 patients with colon cancer showed higher LN yield in the T3+T4 group than in the T1+T2 group (OR=1.41, 95% CI (1.09 to 1.82), p=0.008, I 2 =68.36%) (figure 3 and online supplemental figure 12). 56 57 59 66 Five studies containing 22 254 patients with colorectal cancer showed that more LNs were obtained from the T2 group than the T1 group (OR=1.88, 95% CI (1.26 to 2.79), p=0.002, I 2 =95.09%) (figure 2 and online supplemental figure 13).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In the meta-analysis, seven studies containing 23 297 patients with colorectal cancer revealed higher LN yield in the T3+T4 group than the T1+T2 group (OR=1.57, 95% CI (1.25 to 1.97), p<0.001, I 2 =70.46%) (figure 2 and online supplemental figure 11). 13 56–59 66 67 Likewise, four studies with 21 293 patients with colon cancer showed higher LN yield in the T3+T4 group than in the T1+T2 group (OR=1.41, 95% CI (1.09 to 1.82), p=0.008, I 2 =68.36%) (figure 3 and online supplemental figure 12). 56 57 59 66 Five studies containing 22 254 patients with colorectal cancer showed that more LNs were obtained from the T2 group than the T1 group (OR=1.88, 95% CI (1.26 to 2.79), p=0.002, I 2 =95.09%) (figure 2 and online supplemental figure 13).…”
Section: Resultsmentioning
confidence: 98%
“…13 56–59 66 67 Likewise, four studies with 21 293 patients with colon cancer showed higher LN yield in the T3+T4 group than in the T1+T2 group (OR=1.41, 95% CI (1.09 to 1.82), p=0.008, I 2 =68.36%) (figure 3 and online supplemental figure 12). 56 57 59 66 Five studies containing 22 254 patients with colorectal cancer showed that more LNs were obtained from the T2 group than the T1 group (OR=1.88, 95% CI (1.26 to 2.79), p=0.002, I 2 =95.09%) (figure 2 and online supplemental figure 13). 12 14 50 61 63 In addition, 4 studies containing 44 563 patients with colorectal cancer showed that more LNs were obtained from the T3 group than the T1 group (OR=2.96, 95% CI (1.50 to 5.85), p=0.002, I 2 =98.26%) (figure 2 and online supplemental figure 14),12 14 50 63 and 4 studies containing 10 211 patients with colorectal cancer showed that more LNs were obtained from the T4 group than the T1 group (OR=3.95, 95% CI (2.14 to 7.27), p=0.002, I 2 =92.50%) (figure 2 and online supplemental figure 15).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…No difference was found in LNY between LS and OS. However, Puckett et al [ 15 ] study showed that an open operative approach, when compared to the laparoscopic approach, was associated with 15% greater odds of retrieval of >12 LNs (OR 1.148; 95% CI (1.035-1.272); p = 0.008).…”
Section: Discussionmentioning
confidence: 99%